The impact of value co-creation on service supply chain performance: a proposed conceptual framework - Jaludin Janteng; Cheng, Ling Tan; Yudi Fernando (Universal Publishers, 2017)
Purpose: This study aims to propose a conceptual framework that link value co-creation, service innovation capability and service supply chain performance. Design/ methodology/ approach: We performed an extensive literature review in the field of service supply chain performance with its various determinants in order to draw a conceptual framework. Findings: The findings of the proposed determinants of service supply chain performance suggest that there is a positive relationship between value co-creation in improving the service supply chain performance, in particular interaction through dialogue, close discussions and collaboration with customers. Research limitations/ implications: The initial observation shows that studies on service supply chain performance are limited in the literature. This allows a deeper understanding of the relationship between value co-creation, service innovation capability, and service supply chain performance of service organisations. Practical implications: This study contributes to additional knowledge and ideas to firms when applying the newly developed value co-creation concept. The positive evidence of its linkages for improving the service supply chain performance is useful for the practitioners who may need to consider reviewing the current strategies used in their organisations to improve service supply chain performance and adopt the proposed determinants. Originality/ value: The contributions of this study is to fill the existing gaps in service chain literature. Additionally, service innovation capability has been used as a mediator that can help to improve the linkages to the service supply chain performance.